BS EN 13203-3. Solar supported gas-fired domestic appliances producing hot water. Appliances not exceeding 70 kW heat input and 500 litres water storage capacity. Part 3. Assessment of energy consumption (11th February 2021) - British Standards Institution,
No abstract available